Pharmacokinetics of boldine in control and Mrp2-deficient rats - Cermanová, Jolana; Prasnicka, A; Doleželová, Eva; Rozkydalova, L; Hroch, Miloš; Chládek, Jaroslav; Tomšík, Pavel; Kloeting, I; Mičuda, Stanislav (Physiological research, 2016)
The aim of the present study was to describe the currently poorly understood pharmacokinetics (PK) of boldine in control rats (LW, Lewis rats), and Mrp2 transporter-deficient rats (TR(-)). Animals from the LW and TR(-) groups underwent a bolus dose study with 10 mg/kg of boldine applied either orally or intravenously in order to evaluate the major PK parameters. The TR(-) rats demonstrated significantly reduced total clearance with prolonged biological half-life (LW 12+/-4.6 versus TR(-) 20+/-4.4 min), decreased volume of distribution (LW 3.2+/-0.4 l/kg versus TR(-) 2.4+/-0.4 l/kg) and reduced bioavailability (LW 7 % versus TR(-) 4.5 %). Another set of LW and TR(-) rats were used for a clearance study with continuous intravenous administration of boldine. The LW rats showed that biliary and renal clearance formed less than 2 % of the total clearance of boldine. The treatment of samples with beta-glucuronidase showed at least a 38 % contribution of conjugation reactions to the overall clearance of boldine. The TR(-) rats demonstrated reduced biliary clearance of boldine and its conjugates, which was partly compensated by their increased renal clearance. In conclusion, this study presents the PK parameters of boldine and shows the importance of the Mrp2 transporter and conjugation reactions in the elimination of the compound.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Animals; Rats, Inbred Lew; krysa rodu Rattus; antiflogistika nesteroidní; zvířata; Aporphines; Rats; ATP-Binding Cassette Transporters; ABC transportéry; aporfiny; potkani inbrední LEW